Urban stormwater management for property development projects in Selangor and Negeri Sembilan - Abdullah, Mohd. Yazid (2006)
Rapid urbanizations and its consequent increase in impervious surfaces and changes in land use generally resulted in problem of flooding and heavy pollution of urban water system and other receiving waters. Urban drainage practice and control philosophy has been based on solving localized floods by transferring excessive flows into the drainage systems downstream. The consequence of removing the stormwater from the land surface so quickly is to increase volumes and peak discharge, overloading the drainage system. This causes severe flooding to downstream areas and a threat to the ecosystem and environment. Since 2001, Urban Stormwater Management Manual for Malaysia (MASMA) was introduced by Drainage Irrigation Department of Malaysia and approved by the Cabinet for the application to replace the earlier manual for storm water management in urban areas. The focus of this study is on the implementation of MASMA in property development projects. The objective of this study is to investigate and identify the problems encountered in its implementation. The study also identifies its effects on project cost and time and benefit of MASMA compliance to property development projects. The methodology adopted involving literature search, interviews with authorities, consultants, developers, contractors and property owners and questionnaire survey to the project engineers. Frequency Analysis and Relative Index analyses were used to analyze the data. The study is limited to on going and completed property development projects of 10 Ha and above in the states of Selangor and Negeri Sembilan only. In conclusion, the problems encountered at MASMA implementation to property development projects have been identified. It includes the identification of cost and time implications on MASMA compliance to the project. Various benefits of MASMA compliance to the developers and property owners have also been identified. Several recommendations are proposed to enhance MASMA application.